DESIGN AND VALIDATION OF CULTURAL QUARTET CARDS ON SOCIO-CULTURAL DIVERSITY MATERIAL FOR STUDENTS IN JUNIOR HIGH SCHOOL - Khusnul Khotimah; Kurniawan, Novian Candra Kurniawan; I Nyoman Ruja (Buletin Literasi Budaya Sekolah, 2025)
Learning media plays an important role in attracting students' interest in the classroom. Quartet cards are one of the media that can be used as teaching materials. Therefore, the purpose of this research is to develop learning media using quartet cards. The method used in developing this media is research and development (R&D) with the planning, production, evaluation (PPE) model. The approach used in this research is a quantitative qualitative approach or Mixed Methods. The limitation contained in this research is to produce a product without any field trials. Assessments from media and material validators are a reference in the development of this media. The results showed that the material validator gave an average assessment of 90%, while the media validator gave an assessment of 92%, which was classified as very suitable for use. So that this learning media has been assessed for its feasibility by validators so that it can be used by students at SMP 11 Malang.